KARAKTERISITIK ORGANOLEPTIK BAKSO IKAN GABUS DENGAN PENAMBAHAN PATI JAGUNG DAN TEPUNG TAPIOKA - Mardesci, Hermiza; Imaryana, Imaryana (Marinade, 2021)
Snakehead fish is one type of fish that is widely found in Indragiri Hilir which is known as â€œharuanâ€ fish. This fish has high economic value if it is processed into processed food products, such as meatballs. Processing of snakehead fish into meatballs can be done by adding other ingredients, such as tapioca flour, sago flour, corn starch, and other flours. This study aims to determine the effect of adding corn starch and tapioca flour to the organoleptic characteristics of the resulting snakehead fish meatballs. The results showed that the snakehead balls most favored by the panelists were snakehead fish balls with the addition of 7.5% corn starch and 2.5% tapioca flour by weight of the ingredients.